2022
DOI: 10.1007/s10140-022-02108-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute disseminated encephalomyelitis in a patient with monkeypox: a case report and radiological findings

Abstract: Monkeypox is a zoonosis caused by a double-stranded DNA virus of the Poxviridae family. It currently represents a global epidemic given its contagion reported in more than 31 previously non-endemic countries. We present the case of a 30-yearold male patient from Peru with a diagnosis of monkeypox by PCR test, who manifested an initial clinical picture of asthenia, adynamia, and odynophagia, with the appearance of pustular lesions on the lower lip and in the genital region associated with motor and sensory defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[23] Similarly, industrialization and the movement of people around the world increases close human-to-animal contact. [24] Previous studies predicted that https://doi.org/10.54724/lc.2023.e3 9 / 11 the climate crisis will increase the number of virus transmission between animals by more than 15,000 over the next 50 years, and even if global warming controlled to occur within 2 degrees Celsius, the risk of infection increases as 3,139 species of habitats move by 2070. [25] To prevent the recurrence of existing diseases such as mpox and the spread of new diseases, future studies to understand the causes and mechanisms of spillover and to preserve biodiversity on a global level is essential.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Similarly, industrialization and the movement of people around the world increases close human-to-animal contact. [24] Previous studies predicted that https://doi.org/10.54724/lc.2023.e3 9 / 11 the climate crisis will increase the number of virus transmission between animals by more than 15,000 over the next 50 years, and even if global warming controlled to occur within 2 degrees Celsius, the risk of infection increases as 3,139 species of habitats move by 2070. [25] To prevent the recurrence of existing diseases such as mpox and the spread of new diseases, future studies to understand the causes and mechanisms of spillover and to preserve biodiversity on a global level is essential.…”
Section: Discussionmentioning
confidence: 99%
“…From 1985 to 2021, serious neurological manifestations, including confusion, seizures and encephalitis, have been recorded in around 3% of MPXV infected patients 5 , including one fatal case 6 . Since May 2022, encephalitis has been diagnosed in several patients affected by MPXV infection [7][8][9][10][11][12][13][14] , including two young, healthy men that died following the complications 7 . Animal studies have suggested neuroinvasive potential of MPXV, detecting viral DNA in the brain of several rodent species [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%